Skeletal diseases caused by mutations in PTH1R show aberrant differentiation of skeletal progenitors due to dysregulation of DEPTOR - Csukasi, Fabiana; Bosakova, Michaela; Barta, Tomas; Martin, Jorge H.; Arcedo, Jesus; Barad, Maya; Rico-Llanos, Gustavo A.; Zieba, Jennifer; Becerra, Jose; Krejci, Pavel; Duran, Ivan; Krakow, Deborah (Frontiers in Cell and Developmental Biology, 2023)
Alterations in the balance between skeletogenesis and adipogenesis is a pathogenic feature in multiple skeletal disorders. Clinically, enhanced bone marrow adiposity in bones impairs mobility and increases fracture risk, reducing the quality of life of patients. The molecular mechanism that underlies the balance between skeletogenesis and adipogenesis is not completely understood but alterations in skeletal progenitor cells’ differentiation pathway plays a key role. We recently demonstrated that parathyroid hormone (PTH)/PTH-related peptide (PTHrP) control the levels of DEPTOR, an inhibitor of the mechanistic target of rapamycin (mTOR), and that DEPTOR levels are altered in different skeletal diseases. Here, we show that mutations in the PTH receptor-1 (PTH1R) alter the differentiation of skeletal progenitors in two different skeletal genetic disorders and lead to accumulation of fat or cartilage in bones. Mechanistically, DEPTOR controls the subcellular localization of TAZ (transcriptional co-activator with a PDZ-binding domain), a transcriptional regulator that governs skeletal stem cells differentiation into either bone and fat. We show that DEPTOR regulation of TAZ localization is achieved through the control of Dishevelled2 (DVL2) phosphorylation. Depending on nutrient availability, DEPTOR directly interacts with PTH1R to regulate PTH/PTHrP signaling or it forms a complex with TAZ, to prevent its translocation to the nucleus and therefore inhibit its transcriptional activity. Our data point DEPTOR as a key molecule in skeletal progenitor differentiation; its dysregulation under pathologic conditions results in aberrant bone/fat balance.